Melanotic Neuroectodermal Tumor of Infancy, a Rapidly Growing Maxillary Alveolar Mass: A Case Report - Atarbashi-Moghadam, Saede (J Dent (Shiraz), 2020)
Melanotic neuroectodermal tumor of infancy is a rare, rapidly growing, painless, pigmented neoplasm with neural crest derivation. It usually occurs during the first year of life and there is a prominent predilection for the maxilla. The purpose of the present report is to describe additional case of melanotic neuroectodermal tumor of infancy of maxilla in a 6-month-old infant male. The treatment included surgical excision with safe margins. No attempt was made for immediate grafting of the surgery site due to high proliferation rate of tissues and self-renewal during infancy. The facial growth was normal and the surgical cleft was tightly closed. Due to the rarity of tumor, essential knowledge on characteristics of this lesion would contribute to a proper diagnosis and benefit treatment planning.